Incretin hormone agonists as promising antiobesity drugs - review of literature - Grzegorczyk, Aleksandra; Korus, Justyna; Dziedziak, Marta; Dardzińska, Nicol; Hopej, Natalia (Journal of Education, Health and Sport, 2025)
The aim of this work is to draw attention to the recently growing problem of obesity and complications related to it. Dietary recommendations and recommendations regarding physical activity turned out not to show satisfactory effects in patients with obesity in terms of weight loss, but also in maintaining the effects of the actions taken. The basic basis of the problem turned out to be much more complicated. It is not only related to the occurrence of a positive energy balance, but also to the dysfunction of the entire organism. The discovery of incretin hormones and their complex mechanism of action gave a new direction to the treatment of metabolic diseases. The drugs presented below act on the incretin receptor, stimulating it and causing an effect that leads to weight loss.